The Effect Of Giving Nano Herbal Biwa Leaf (Eriobotrya japonica Lindl.) Against Histological Description Of Kidney Rat That Induced By Alloxan - Syafruddin Ilyas (Talenta Publisher, 2021)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia due to abnormal insulin secretion and insulin action. Uncontrolled diabetes mellitus will cause various organ complications, one of which is diabetic nephropathy or kidney failure. The aim of this study was to determine the effect of nano herbal of biwa leaves (Eriobotrya japonica) on the structure of gromerulus, renal necrosis, proximal tubular constriction, kidney weight and kidney discoloration. This study uses an analytic study with a true experimental design in male rats (Rattus norvegicus) consisting of five treatments with each of six replications. This study consisted of a negative control group that was only given ad-libitum feed, a positive control injected with alloxan, and two groups injected with alloxan and given a 250 mg/kg and 500 mg/kg biwa nanoherbal. It was concluded that the nanoherbal of biwa leaves is effective enough to reduce blood glucose levels and is safe for consumption by diabetics because it does not damage kidney cells.